2020
DOI: 10.7717/peerj.9997
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution modelling of Bryde’s whales, humpback whales, southern right whales, and sperm whales in the southern African region to inform their conservation in expanding economies

Abstract: In southern African waters, information about species distribution and habitat preferences of many cetacean species is limited, despite the recent economic growth that may affect them. We determined the relative importance of eight environmental variables (bathymetry, distance to shore, slope, chlorophyll-a, salinity, eastwards sea water velocity, northwards sea water velocity and sea surface temperature) as drivers of seasonal habitat preferences of Bryde’s whales (Balaenoptera brydei), humpback whales (Megap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…The high acoustic occurrence of sperm whales obtained from AARs 2 and 3 deployed at 1118 m water depth suggests that this water depth is one of the preferred and more important habitats, as indicated by whale catches where more whales were caught inhabiting water depths of 1000 m than 4000 m (Best 1999). AAR4 deployed at 4481 m water depth produced the lowest percentage of sperm whale acoustic occurrence, indicating that a small proportion of this species occupies this deep sea area, as similarly indicated by whale catches (Best 1999) and species distribution modelling (Purdon et al 2020b). Furthermore, sperm whale clicks produced at great depths could have been deflected by the thermocline (an acoustic barrier) and prevented from reaching AARs 1 and 4, as these 2 recorders were sometimes positioned above or below the thermocline depth (~200 m depending on season; Shabangu et al 2020c).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The high acoustic occurrence of sperm whales obtained from AARs 2 and 3 deployed at 1118 m water depth suggests that this water depth is one of the preferred and more important habitats, as indicated by whale catches where more whales were caught inhabiting water depths of 1000 m than 4000 m (Best 1999). AAR4 deployed at 4481 m water depth produced the lowest percentage of sperm whale acoustic occurrence, indicating that a small proportion of this species occupies this deep sea area, as similarly indicated by whale catches (Best 1999) and species distribution modelling (Purdon et al 2020b). Furthermore, sperm whale clicks produced at great depths could have been deflected by the thermocline (an acoustic barrier) and prevented from reaching AARs 1 and 4, as these 2 recorders were sometimes positioned above or below the thermocline depth (~200 m depending on season; Shabangu et al 2020c).…”
Section: Discussionmentioning
confidence: 66%
“…For example, AARs 3 and 4 had the same sampling protocol and were deployed within the same period but at different water depths (1118 m for AAR3 versus 4481 m for AAR4); however, AAR3 produced more hours with sperm whale clicks than AAR4. Purdon et al (2020b) found water depths between 750 and 1500 m and a distance to shore of approximately 130 km to have the highest effect on sperm whale distribution in the southern African region. Moreover, AAR3 had a higher detection range than AAR4 due to variations in ambient noise between the 2 positions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, the high number of detections of gunshot sounds from AAR1 (the more coastal listening station deployed at 855 m water depth) could be due to high prey densities and favorable environmental conditions associated with that depth (Elwen & Best, 2004a, b;Prieto et al, 2017;Purdon et al 2020;Shabangu et al, 2019). For example, areas shallower than the 1,000 m isobath on the west coast of South Africa are known to have elevated productivity to support high biomasses of prey due to increased upwelling (Andrews & Hutchings, 1980;Lamont et al, 2015Lamont et al, , 2018.…”
mentioning
confidence: 99%